Scour evolution downstream of submerged weirs in clear water scour conditions - Guan, Dawei (2020)
Although weirs or dikes in the riverine and coastal environments are frequently overtopped, few studies have hitherto examined the evolution of the scour process downstream of these structures under the submerged condition. This paper presents an experimental investigation on time evolution of the scour process downstream of submerged weirs with a uniform coarse sand. The clear-water scour experiments were carried out in a tilting recirculation flume. Different flow intensities and overtopping ratios (approach flow depth/weir height) were adopted in the experiments. Experimental observations show that the scour hole downstream of submerged weirs develops very fast in the initial stage, before progressing at a decreasing rate and eventually reaching the equilibrium stage. The results show that an increase of the overtopping ratio or flowrate can generate larger scour depth and volume downstream of the weir. Moreover, geometrical similarity of the scour hole that formed downstream of the weir was observed in the tests. Finally, empirical equations for predicting scour hole geometrical evolutions downstream of the submerged weirs were presented. The results of this study are useful in the development of numerical/analytical models capable of estimating the scour depth downstream of weirs in the river or coastal areas, for which the overtopping conditions are present.